Current growth of internet subscribers in Bangladesh and its benefit towards our economy: a study on Premium Connectivity ltd. (PCL) - Rasel, Md (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.